TIN-BASED ALLOY FOR FUEL CATALYST - Siti Rochani; Pramusanti Pramusanto; Retno Damayanti (Puslitbang tekMIRA, 2013)
Tin-based fuel catalyst, if dipped into a gasoline-containing tank will increase fuel efficiency. The catalyst has been used since 60 years ago. Its usage will save the fuel and increase the use of tin as expected by tin-producers. Though the mechanism of catalytic reaction has not been clearly understood, several research regarding catalyst performance have been conducted. Moreover some companies have already produced such a catalyst. The tin alloy catalyst was made by melting tin and other metals at specific compositions in a burner and casted into dif- ferent shapes. In term of evaluating the contact between the fuel and the catalyst as well as assessing the alloy catalytic mechanism, the samples were dipped in gasoline and stirred for 3 days. The gasoline with and without catalyst were analyzed using infrared and showed that the spectra appeared at 875, 835, 538, 343 and 229 cm-1 after 3-day dipped. The peaks resulted for catalytic interaction between Sn and gasoline. Fuel efficiency was measured through static and dynamic tests. The former was conducted using a genset and lawn mower by running the diesel-containing engines in empty load condition. The result showed that efficiency of catalyst-containing diesel consumption was still low, ranged between 0.6 - 5%. Other static tests were performed at LEMIGAS using Toyota and Isuzu car engines. Using gasoline and diesel respectively. Effect of catalyst on the car with gasoline improves engine capacity to 8.79%, and increases fuel consumption to 1.03%. The catalyst applied the car with diesel enhances the capacity to 11.38 % and increases fuel consumption to 9.39%. Dynamic tests conducted to motor bikes and cars show the efficiency of fuel consumption around 5-17.5%. It means that tin-alloys based catalyst for efficiency of fuel use is prospective. Such a catalyst is easy to be made and utilized.